Five keys to retailers for safer pork in traditional markets in Cambodia - International Livestock Research Institute (International Livestock Research Institute, 2021)
The Safe Food, Fair Food for Cambodia project produced this video to support national food safety authorities and food chain stakeholders in promoting good practices among pork retailers in Cambodia’s traditional markets. Retailers can improve the safety of pork using simple and low-cost hygiene practices, which include ensuring food (pork) is not cross-contaminated, maintaining cleanliness in retail areas, using easy-to-clean materials on tables, and getting certified and trained in food handling. The SFFF Cambodia project is led by ILRI in partnership with the National Animal Health and Production Research Institute, the Livestock Development for Community Livelihood and Emory University, USA.